Do meteorological and road conditions influence animal-vehicle collisions? - Ignatavičius, Gytautas; Ulevičius, Alius; Valskys, Vaidotas; Matačina, Lina (International Conference “Environmental Engineering”, 2026)
Significant uncertainty remains regarding the relationship between meteorological conditions and Animal-Vehicle Collisions (AVCs). This study aimed to evaluate the influence of meteorological and related road conditions on AVC occurrence in Lithuania. Meteorological data and collision records from 56 automatic weather stations were linked with 1,632 AVCs reported between 2018 and 2022. Principal Component Analysis (PCA) revealed that meteorological variables form two statistically significant groups with contrasting associations with AVC occurrence. The first group – characterized by higher air and road surface temperatures, greater visibility, and a higher road adhesion coefficient – was positively associated with AVC occurrence. In contrast, the second group, defined by snow and ice cover, rain intensity, and the presence of water on the road surface, showed a negative association with AVC occurrence. These findings suggest that AVC risk increases under favourable driving conditions, likely due to changes in driver behaviour, whereas adverse weather conditions may reduce collision risk as drivers tend to exercise greater caution. Overall, the results provide new insights into the role of meteorological and road conditions in AVC dynamics and highlight the importance of considering human behavioural responses when developing AVC mitigation strategies.
Keywords: human-wildlife conflict; meteorological conditions; traffic safety